Cardiac symptom burden and arrhythmia recurrence drives digital health use: results from the iHEART randomized controlled trial. (2nd May 2021) - Masterson Creber, Ruth M; Reading Turchioe, Meghan; Biviano, Angelo; Caceres, Billy; Garan, Hasan; Goldenthal, Isaac; Koleck, Theresa; Mitha, Shazia; Hickey, Kathleen; Bakken, Suzanne
Abstract: Aims: Digital health can transform the management of atrial fibrillation (AF) and enable patients to take a central role in detecting symptoms and self-managing AF. There is a gap in understanding factors that support sustained use of digital health tools for patients with AF. This study identified predictors of Alivecor ® KardiaMobile ECG monitor usage among patients with AF enrolled in the i Phone ® H elping E valuate A trial fibrillation R hythm through T echnology (iHEART) randomized controlled trial. Methods and results: We analysed data from 105 English and Spanish-speaking adults with AF enrolled in the intervention arm of the iHEART trial. The iHEART intervention included smartphone-based electrocardiogram self-monitoring with Alivecor ® KardiaMobile and triweekly text messages for 6 months. The primary outcome was use of Alivecor ® categorized as: infrequent (≤5 times/week), moderate (>5 times and ≤11 times/week), and frequent (>11 times/week). We applied multinomial logistic regression modelling to characterize frequency and predictors of use. Of the 105 participants, 25% were female, 75% were White, and 45% were ≥65 years of age. Premature atrial contractions (PACs) [adjusted odds ratio (OR): 1.23, 1.08–1.40, P = 0.002] predicted frequent as compared to infrequent use. PACs (adjusted OR: 1.17, 95% confidence interval 1.06–1.30, P = 0.003), lower symptom burden (adjusted OR: 1.06, 1.01–1.11, P = 0.02), and less treatment concern (adjusted OR: 0.96, 0.93–0.99, P = 0.02) predicted moderate as compared to infrequent use. Conclusions: Frequent use of AliveCor ® is associated with AF symptoms and potentially symptomatic cardiac events. Symptom burden and frequency should be measured and incorporated into analyses of future digital health trials for AF management.